1973
DOI: 10.1111/j.1476-5381.1973.tb08182.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute systemic anaphylaxis in the calf

Abstract: Summary1. Acute systemic anaphylaxis in calves was characterized by marked systemic hypotension; hypertension in the pulmonary arteries and abdominal vena cava, and transient apnoea. Calves responded with a second reaction to antigen, but a third anaphylactic response could not be evoked. 2. Suppression of systemic anaphylaxis could not be effected with mepyramine, whereas methysergide or diethylcarbamazine each suppressed anaphylaxis by 50%. Disodium cromoglycate alone did not inhibit anaphylaxis: however, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
29
0
2

Year Published

1973
1973
2016
2016

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 31 publications
(42 reference statements)
4
29
0
2
Order By: Relevance
“…Previous studies (Arowolo & Eyre, 1980) reported the reactivity of the bronchial artery to histamine, and the immunological release of histamine from calf lung (Eyre, 1971c: Eyre et al, 1973. In addition Eyre & Deline (1971) HT) release from bovine lung during anaphylaxis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies (Arowolo & Eyre, 1980) reported the reactivity of the bronchial artery to histamine, and the immunological release of histamine from calf lung (Eyre, 1971c: Eyre et al, 1973. In addition Eyre & Deline (1971) HT) release from bovine lung during anaphylaxis.…”
mentioning
confidence: 99%
“…Methods Male Jersey calves (1-3 months old) were sensitized to horse serum as previously described (Eyre, Lewis & Wells, 1973). Calves were anaesthetized and killed with sodium pentobarbitone (100 mgkg-1).…”
mentioning
confidence: 99%
“…Activated kallikrein has been implicated in peripheral vascular changes in both P. knowlesi and B. bovis infections . Eyre & Lewis (1972) and Eyre, Lewis & Wells (1973) suggested that kinins contribute significantly to the profound hypotension observed during bovine anaphylactic shock. It is likely that the increased liberation of kinins plays a significant part in the hypotension during B. bovis infections.…”
Section: Discussionmentioning
confidence: 99%
“…After a further three to four weeks the ponies were anaesthetized with 25 mg/kg pentobarbitone sodium, given intravenously, and anaesthesia was maintained with supplementary pentobarbitone. With the animals in right lateral recumbency, blood pressures were recorded and measured in the left common carotid artery, the pulmonary artery and abdominal vena cava, as previously described in calves Eyre, Lewis & Wells, 1973). Respiratory ventilation volume was also monitored as before.…”
Section: Methodsmentioning
confidence: 99%